Star wars : Rey meets BB-8 - Schaefer, Elizabeth (Glendale, California : Lucasfilm Press, 2015)
Scavenger Rey lives a lonely existence on the planet Jakku until a visit by droid BB-8 changes her life forever.
Keywords: Robots -- Juvenile fiction; Extraterrestrial beings -- Juvenile fiction; Star Wars fiction